Human Capital Depreciation in the Pacific Alliance during 2007 - 2014 - Castillo-Aroca, Alberto (2016)
This study estimated the human capital depreciation rate according to gender, age, urban-rural region and economic sector, using the method proposed by Neuman & Weiss (1995). To do this, household surveys of 2007-2014 of the members countries of the Pacific Alliance are employed. The results show that depreciation rates were relatively constant during the observed period. At the same time, women, people over fifty years old, the industrial and services sector, and urban areas have a greater vulnerability to obsolescence.